Greenness in the Eye of Bond Short Sellers - Cao, Jie; Li, Shuting; Zhan, Xintong; Zhang, Weiming (Elaine); Zhou, Linyu (Wiley, 2026)
This paper examines how short sellers value “greenness” in trading corporate bonds. We document significantly higher shorting volumes for green bonds relative to conventional bonds issued by the same firm. We consider several potential explanations, including short-sale constraints and lending market frictions, sources for future price declines, and demand pressure from investors. None of the above could explain the higher shorting volumes for green bonds, leaving an intriguing puzzle.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas ::5311.02 Gestión financiera; ODS 13 - Acción por el clima; Corporate green bonds; short sellers; short-sale constraints; greenwashing risks